Oil Accumulation and First Fire Readiness Analysis of Cylinder Deactivation - Halbe, Mayura; Pietrzak, Brad; Fain, David; Ramesh, Aswin; Shaver, Greg; McCarthy, James E.; Ruth, Mike; Koeberlein, Edward (Frontiers in Mechanical Engineering, 2017)
Cylinder deactivation (CDA) is a technology that can improve the fuel economy and exhaust thermal management of compression ignition engines (diesel and natural gas), especially at low loads and engine idling conditions. The reduction in engine displacement during CDA improves fuel efficiency at low loads primarily through a reduction in pumping work. During deactivation of a given cylinder the drop in pres- sure inside the cylinder could possibly lead to the transport of oil from the crankcase into the cylinder owing to the reduced pressure difference between the crankcase and the cylinder. In addition, cylinder deactivation might inhibit the first fire readiness of a reactivating cylinder as a result of reduced wall, head, and piston temperatures. Both of these potential issues are quantitatively studied in this paper. This paper describes a strategy to estimate in-cylinder oil accumulation during CDA, and first fire readiness following CDA, through comparison of individual heat realease profiles before and after CDA. Cylinder cool-down and oil accumulation dur- ing deactivation could possibly result in misfire or degraded combustion upon an at- tempt to reactivate a given cylinder. Fortunately, experiments described in this paper demonstrate no cases of misfire at any speed/load conditions for the CDA durations tested, specifically, 100 ft-lb load at 800 rpm and 1200 rpm with deactivation intervals of 0.5, 5, 10 and 20 minutes. Although pilot heat release in the reactivated cylinders was delayed by approximately 1 CAD after 5 minutes of CDA, the main heat release was very similar to the heat release of a continuously activated cylinder. As such, results show no first fire readiness issues at the conditions tested. The duration of time the engine could be operated in CDA mode without significant oil accumulation, and other methods to minimize oil accumulation during CDA have also been proposed.